Nine modern muses: Women and the nobel prize for literature - González Parra, Diana Lucia; González Parra, María Patricia
Nine Modern Muses: Women and the Nobel Prize for Literature is a biographical work which focuses upon the Greek Muses, Alfred Nobel´s life and the Nobel Prize. It also deals with the lives and literary productions of the women winners of the Nobel Prize for Literature: Selma Lagerlöf, Grazia Deledda, Sigrid Undset, Nadine Gordimer, Nelly Sachs, Wislawa Szymborska, Gabriela Mistral, Pearl Buck and Toni Morrison. Additionally, it contains an analysis of some novels and cites some poems of these winners